Avaliação da temperatura de cristalização da parafina em sistemas: parafina, solvente e tensoativo - Santana, Erika Adriana de (2005)
The formation of paraffin deposits is common in the petroleum industry during production, transport and treatment stages. It happens due to modifications in the thermodynamic variables that alter the solubility of alkanes fractions present in petroleum. The deposition of paraffin can provoke significant and growing petroleum losses, arriving to block the flow, hindering to the production. This process is associated with the phases equilibrium L-S and the stages and nucleation, growth and agglomeration the crystals. That process is function of petroleum intrinsic characteristics and temperature and pressure variations, during production. Several preventive and corrective methods are used to control the paraffin crystallization, such as: use of chemical inhibitors, hot solvents injection, use of termochemistry reactions, and mechanical removal. But for offshore exploration this expensive problem needs more investigation. Many studies have been carried through Wax Appearance Temperature (WAT) of paraffin; therefore the formed crystals are responsible for the modification of the reologics properties of the oil, causing a lot off operational problems. From the determination of the WAT of a system it is possible to affirm if oil presents or not trend to the formation of organic deposits, making possible to foresee and to prevent problems of wax crystallization. The solvent n-paraffin has been widely used as fluid of perforation, raising the production costs when it is used in the removal paraffin deposits, needing an operational substitute. This study aims to determine the WAT of paraffin and the interference off additives in its reduction, being developed system paraffin/solvent/surfactant that propitiates the wax solubilization. Crystallization temperatures in varied paraffin concentrations and different solvents were established in the first stage of the experiments. In the second stage, using the methodology of variation of the photoelectric signal had been determined the temperature of crystallization of the systems and evaluated the interferences of additives to reduction of the WAT. The experimental results are expressed in function of the variations of the photoelectric signals during controlled cooling, innovating and validating this new methodology to determine WAT, relatively simple with relation the other applied that involve specific equipments and of high cost. Through the curves you differentiate of the results had been also identified to the critical stages of growth and agglomeration of the crystals that represent to the saturation of the system, indicating difficulties of flow due to the increase of the density